2021
DOI: 10.3390/nano11112898
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability, Blocking Regime and Superparamagnetic Behavior in Mn-Al-C Melt Spun Ribbons

Abstract: Alloys possessing nominal compositions Mn53Al45C2 and Mn52Al46C2 were prepared by the melt spinning method and were subjected to complex structural, morphological and magnetic investigations. As these alloys can exhibit tetragonal L10-type and τ phase, they have good potential as rare earth (RE)—free magnets. It is, therefore, important to monitor the ε–τ phase transformation and the stability and the magnetic features of the tetragonal phase in an entire temperature interval. By using synchrotron X-ray diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Alina Crisan et al reported on the synthesis, morpho-structural characterization, thermal stability and superparamagnetic behavior of Mn–Al–C melt-spun ribbons [ 8 ]. It is well known that the Mn–Al binary alloy has recently attracted significant interest as a potential solution for low-cost, rare-earth-free, permanent magnets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Alina Crisan et al reported on the synthesis, morpho-structural characterization, thermal stability and superparamagnetic behavior of Mn–Al–C melt-spun ribbons [ 8 ]. It is well known that the Mn–Al binary alloy has recently attracted significant interest as a potential solution for low-cost, rare-earth-free, permanent magnets.…”
mentioning
confidence: 99%
“…While different phases can appear in Mn–Al or Fe–Pt alloys, and only one type is effective for hard magnetic properties, it becomes interesting to monitor the phase transformation and phase stability in Mn–Al melt-spun ribbons (whose degrees of freedom are additionally increased by the third element, C) with respect to processing conditions and thermal treatments. Finally, the magnetic behavior in correlation to structural changes and phase composition and stability was reported in [ 8 ].…”
mentioning
confidence: 99%